Sustainable development concepts, methodologies, tools, and applications (Information Science Reference, 2018)
"This book is a comprehensive source of scholarly information on the latest research for sustainability concerns across a multidisciplinary perspective. Highlighting a broad range of innovative topics such as renewable energy, urban development, and green technologies"--